Bounding quantile demand functions using revealed preference inequalities - Richard Blundell; Dennis Kristensen; Rosa Matzkin (Centre for Microdata Methods and Practice (cemmap), 2011)
This paper develops a new technique for the estimation of consumer demand models with unobserved heterogeneity subject to revealed preference inequality restrictions. Particular attention is given to nonseparable heterogeneity. The inequality restrictions are used to identify bounds on quantile demand functions. A nonparametric estimator for these bounds is developed and asymptotic properties are derived. An empirical application using data from the U.K. Family Expenditure Survey illustrates the usefulness of the methods by deriving bounds and confidence sets for estimated quantile demand functions.
Keywords: C20; D12; 330; consumer behaviour; revealed preference; bounds; quantile regression; Offenbarte Präferenzen; Schätztheorie